Tuna sector - Issues and challenges: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Tuna products sold in the EU (the largest world market for tuna products, mainly sold in canned form), come from countries where EU companies have invested in processing facilities and where the EU has bilateral fishing agreements or private licensing agreements. This Executive Brief examines the main tuna sector trends at global and EU levels, with special attention to the implications for ACP countries. Issues such as the growing EU regulatory requirements on SPS standards and illegal, unreported and unregulated (IUU) fishing, as well as the sustainability concerns in tuna fisheries management and the introduction of equity criteria along the tuna processing chain, are broadly discussed.